Advances in pharmacotherapies for movement disorders in children: current limitations and future progress. Issue 6 (December 2017) - Lin, Jean-Pierre
Abstract : Purpose of review: In childhood, movement disorders are generated by a very large number of disorders of the nervous system, and the very different developmental ages at which these occur make studies of pharmacotherapy efficacy extremely difficult. In most clinical practices, medication used in management is by trial and error, and limited by lack of efficacy and/or adverse drug reactions leading to drug intolerance. Nevertheless, symptom reduction using polypharmacy must be balanced against any accompanying comorbidities such as poor attention and concentration, constipation, ileus, urinary retention, blurred vision sedation and respiratory depression. Recent findings: A 'personalised medicine' approach may lead to specific management breakthroughs that are beneficial to a wider number of children. At present, neuromodulation with implantable devices offers greater proven efficacy for dystonia, myoclonus and dystonic-choreoathetosis, but enteral, intravenous and, more recently, transdermal medication strategies with clonidine patches and enteral gabapentin may provide important relief for both home management and critical care settings. Summary: The current review brings the clinician up-to-date with the latest, albeit limited, thinking on the pharmacological management of movement disorders in children by focussing on goal-directed outcome measures to improve clinical decision-making in an evidence-light clinical setting.